2018
DOI: 10.1107/s1600577517015466
|View full text |Cite
|
Sign up to set email alerts
|

Transient thermal stress wave and vibrational analyses of a thin diamond crystal for X-ray free-electron lasers under high-repetition-rate operation

Abstract: High-brightness X-ray free-electron lasers (FELs) are perceived as fourth-generation light sources providing unprecedented capabilities for frontier scientific researches in many fields. Thin crystals are important to generate coherent seeds in the self-seeding configuration, provide precise spectral measurements, and split X-ray FEL pulses, etc. In all of these applications a high-intensity X-ray FEL pulse impinges on the thin crystal and deposits a certain amount of heat load, potentially impairing the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the case of intense pulses with high repetition rates, one should also consider the emerging transient thermal strain waves. It has been shown that the impact of these waves can become critical for ultra-thin diamond crystals with thickness of $10 mm and repetition rates of 100 kHz and above (Yang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of intense pulses with high repetition rates, one should also consider the emerging transient thermal strain waves. It has been shown that the impact of these waves can become critical for ultra-thin diamond crystals with thickness of $10 mm and repetition rates of 100 kHz and above (Yang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The quasi-static three-dimensional effect of pulsed heat load in a Bragg reflector has been investigated in detail for low temperatures (Qu et al, 2021). Dynamic three-dimensional wave propagation has been investigated theoretically by Yang et al (2018) and Qu (2020) using numerical approaches. Three-dimensional wave propagation at low temperatures has been investigated experimentally and theoretically in the context of a PhD project (Bahns, 2021), which is related to the topic of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Bushuev applied his model to estimate the performance of the self-seeding crystal monochromator of the European XFEL. Yang et al [ 17 ] investigated the transient thermal stress wave and vibration to describe the thermomechanical issues for thin diamond crystals under high-repetition-rate operation of an XFEL, but no further analysis was carried out about the distortion of the rocking curve induced by the non-uniform thermal load. Based on Bushuev’s work, Qu et al [ 18 ] further formulated the factors (such as the maximum strain and non-uniform thermal load) that affect the central wavelength shift and the distortion of the rocking curve, and they discussed these effects separately and quantitatively by an analytical method.…”
Section: Introductionmentioning
confidence: 99%